Kesesuaian dan Arahan Penggunaan Lahan Berdasarkan Rencana Pola Ruang Wilayah di Hulu Daerah Aliran Sungai Kelara - Usman Arsyad; Andang Suryana Soma; Wahyuni Wahyuni; Tita Rahayu Arief (Fakultas Kehutanan, Universitas Hasanuddin, 2017)
This study aimed to analyze the compatibility between the land cover spatial pattern plan and determine the direction of land use in the event of a discrepancy. This research was conducted on the Kelara Upstream Watershed located in gowa and jeneponto using land cover maps generated from landsat imagery interpretation 8. Then overlay to map the spatial pattern plan. Then determined the order of land use is done when there is a discrepancy between the results of the overlay with maps of land cover spatial pattern plan. The result showed that 41,05% of the total area of the Kelara Upstream Watershed of 28.185,68 ha a land use form of a orchards. After overlay discovered discrepancy land cover maps with maps of spatial pattern plan. Based on a map spatial pattern plan that should in reality the field is man made forest, orchards, dryland agriculture and rice field. According to these condition the specified order of land use that is Hkm (Community Forest) with agroforestry and Agroforestry Systems. Rice field In the Protected and Production forest order to intensification land use and plantations forest, orchards and dry land agriculture order to Community Forest with agroforestry systems . In the area of cultivation the land use rice field, orchards and dryland agriculture order to agroforestry systems.